Discharge characteristics of ground potential live-line work air gaps in cup towers and double circuit towers. (August 2022) - Gao, Jiachen; Wang, Linong; Li, Guanlin; Wu, Shaocheng; Song, Bin; Xie, Cheng; Liu, Lei; Wang, Tingting
Abstract: Ground potential live-line work (GPLW) is an irreplaceable means for the maintenance and elimination of overhead transmission lines. In order to put forward safety protection suggestions for GPLW, the dielectric strength of the GPLW gaps in cup towers and double circuit towers were studied based on a prediction method. The results showed that in both cup towers and double circuit towers, as the gap distance increases, the dielectric strength will also increase. In cup towers, when the lineman is on the side of the window, standing inside the window will increase the dielectric strength of GPLW gaps. When the lineman is at the bottom of the tower window, raising hands will reduce the dielectric strength of GPLW gaps, but this will not happen on the side or top of the tower window. In double circuit towers, the position and posture of the lineman have little effect on the dielectric strength of GPLW air gaps. The results of the study could provide guidance for the live-line work engineering.